Recruitment of the rhizo-microbiome army: assembly determinants and engineering of the rhizosphere microbiome as a key to unlocking plant potential - Park, Inmyoung; Seo, Young-Su; Mannaa, Mohamed (Frontiers in Microbiology, 2023)
The viable community of microorganisms in the rhizosphere significantly impacts the physiological development and vitality of plants. The assembly and functional capacity of the rhizosphere microbiome are greatly influenced by various factors within the rhizosphere. Primary factors are the host plant genotype, developmental stage and status, soil properties, and the resident microbiota. These factors drive the composition, dynamics, and activity of the rhizosphere microfloramicrobiome. This review addresses the intricate interplay between these factors and how it facilitates the recruitment of specific microbes by the host plant to support plant growth and resilience under stress. This review also explores current methods for engineering and manipulating the rhizosphere microbiome, including host plant-mediated manipulation, soil-related methods, and microbe-mediated methods. Advanced techniques to harness the plant's ability to recruit useful microbes and the promising use of rhizo-microbiome transplantation are highlighted. The goal of this review is to provide valuable insights to the current knowledge, which will facilitate the development of cutting-edge strategies for manipulating the rhizosphere microbiome for enhanced plant growth and stress tolerance. The article also indicates promising avenues for future research in this field.